Optimalisasi Zona Perkembangan Proksimal dalam Pembelajaran Berbasis Budaya Lokal untuk Mengembangkan Keterampilan Sosial Anak Usia Dini - Nurafni Umayyah; Fauzi Fauzi (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
Early childhood social skills often do not develop optimally because learning does not provide adequate support for developmental needs and does not make the most of local culture as a learning resource. This study aims to optimizing ZPD in local culture-based learning to strengthen children's social skills. The research was conducted at the Muslimat NU Masyithoh 25 Sokaraja early childhood education center in Banyumas district with the research subjects being children aged 4-6 years and teachers involved in the learning process. The type of research used was descriptive qualitative research with a field study approach. Data were collected through observation of children's interactions, interviews with teachers, and documentation of learning activities that utilized elements of local culture. Data analysis was conducted through data reduction, data presentation, and inductive conclusion drawing to obtain an overview of the learning patterns and development of children's social skills. The results of the study indicate that the integration of local culture can improve cooperation, communication skills, and children's ability to build social relationships more effectively. These findings confirm that analysis of the application of the Zone of Proximal Development (ZPD) in the context of local culture-based learning contributes significantly to strengthening the social skills of early childhood